PESAN MORAL DAN MOTIVASI DALAM NOVEL JANJI UNTUK AYAH KARYA NURUNALA - Wahidah, Alifah Nur; Paulina, Yanti; Hakim, Man; Atmaja, Loliek Kania (Jurnal Membaca Bahasa dan Sastra Indonesia, 2025)
The problem in this researchis the Moral and Motivational Messages contained in the characters of the novel Janji Untuk Ayah by Nuranala. The purpose of this research, namely: To get a precise description, detailed and in-depth description of the categories of moral and motivational messages contained in the characters of the novel Janji Untuk Ayah by Nurunala. For Father by Nurunala. The benefits of research are divided into two, namely theoretical benefits, namely, the results of this study are expected to be used as a review for understand the categories and aspects of moral messages in Nurunala's Janji Untuk Ayah and contribute to the development of literary works. development of literary works and practical benefits, namely, for readers, for students, and for further researchers. students, and for further researchers. The data in this research is in the form of quotations that contain moral message categories and motivational aspects contained in the characters in the novel Janji Untuk Ayah by Nurunala. The data collection technique of this research is library study technique. The result of The result of this research is that there is a moral message of human relationship with God, human relationship with self, human relationship with self, and human relationship with self. human relationship with self, human relationship with other human beings, and human relationship with nature. While the motivation aspect is found to be motivated to act.